451 градус по Фаренгейту - Брэдбери Рэй (Интеллектуальный бестселлер, 2015)
Экземпляры: ф.10 (20151013) / Инвентарный номер: 56623 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Б 89 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44